2011
DOI: 10.1186/1471-2229-11-57
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, genetic and transcriptional evidence for a role of VvAGL11 in stenospermocarpic seedlessness in grapevine

Abstract: BackgroundStenospermocarpy is a mechanism through which certain genotypes of Vitis vinifera L. such as Sultanina produce berries with seeds reduced in size. Stenospermocarpy has not yet been characterized at the molecular level.ResultsGenetic and physical maps were integrated with the public genomic sequence of Vitis vinifera L. to improve QTL analysis for seedlessness and berry size in experimental progeny derived from a cross of two seedless genotypes. Major QTLs co-positioning for both traits on chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
174
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(205 citation statements)
references
References 68 publications
16
174
1
3
Order By: Relevance
“…The availability of the grapevine genome sequence combined with the advent of cheaper and high throughput single nucleotide polymorphism (SNP) genotyping strategies (Gupta et al 2008;Davey et al 2011) were expected to shift the tools of genetic studies in grapevine. However, microsatellites are still the predominant markers contributing to the current knowledge of genetic determinism of the major grapevine traits (Mejía et al 2011;Huang et al 2012;Duchêne et al 2012;Karaagac et al 2012;Doligez et al 2013;Battilana et al 2013;Grzeskowiak et al 2013;Ban et al 2014;Correa et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The availability of the grapevine genome sequence combined with the advent of cheaper and high throughput single nucleotide polymorphism (SNP) genotyping strategies (Gupta et al 2008;Davey et al 2011) were expected to shift the tools of genetic studies in grapevine. However, microsatellites are still the predominant markers contributing to the current knowledge of genetic determinism of the major grapevine traits (Mejía et al 2011;Huang et al 2012;Duchêne et al 2012;Karaagac et al 2012;Doligez et al 2013;Battilana et al 2013;Grzeskowiak et al 2013;Ban et al 2014;Correa et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1) located on chromosome 18 (Cabezas et al 2006;Costantini et al 2008;Mejía et al 2007, http://www.genoscope.cns.fr/externe/GenomeBrowser/ Vitis/). Recently, Mejía et al (2011) have identified additional microsatellite markers closely linked to SDI, but this information was not available when the study was carried out, 5 years ago. Simultaneous genotyping for the three loci was performed using a multiplex PCR protocol with forward primers labeled with fluorochromes (6-FAM, VIC, and NED for VMC7F2, VVIN16, and UDV-108, respectively) and ABI-Prism 3130 sequencer (Applied Biosystems).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Although these markers could help to predict seedlessness, the presence of null alleles and the weak linkage with the SDI locus compromises their use in many genetic backgrounds Korpas et al 2009). The third one is the microsatellite VMC7F2 (Cabezas et al 2006), a gene specific marker located 463 bp upstream of the predicted ORF for VvAGL11, proposed as the candidate gene responsible for this major effect QTL (Mejía et al 2011). QTL analyses showed a strong association between the seedlessness donor allele at SDI and a 198-bp allele at this locus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations